The African wife of Abraham (Gn 16:1-16; 21:8-21) - Adamo, David Tuesday (Old Testament essays, 2005)
The purpose of this paper is to establish the Africanness of Hagar, the wife of Abraham. Hagar is a prominent figure in the Hebrew and Islamic traditions, so the paper analyses her place in God's salvific plan. It also places Hagar's marriage in the context of Urhobo customary marriage law. The essay also holds Hagar up as a model for contemporary African women.